Visitor willingness to pay for conservation of ecotourism at Kilim Karst Geoforest, Langkawi, Malaysia. - Mohd Noor, Nur Faizah (2011)
The objective of this research is to investigate the visitor’s willingness to pay (WTP) towards sustainability of ecotourism resources at Kilim Karst Geoforest Park(KKGP) and to determine the level of satisfaction of visitors using the ecotourism resources and facilities at the park. Data are obtained by using a closed-ended and multiple categories questionnaire in a face-to-face interview. The study is based on a sample of 448 respondents that were randomly chosen for face to face interview in KKGP in May to October 2009. The results show that most of the visitors are satisfied with ecotourism resources in KGGP and many are first time visitors to the park while only a few have visited more than once. The data are analyses using descriptive analysis, factor analysis and contingent valuation method (CVM). The factor analysis divides into two parts which is perception and attitude that influenced visitors’ willingness to pay towards sustainability of KKGP ecotourism. For perception, three factors have been identified; natural scenery, utilities and services, and natural environment exploration. While for attitude part, there also three factors have been defined as are protection of natural resources, attraction at KKGP natural resources, and implementation of fee. CVM is used to determine the visitors’ WTP. A logit model is used to determine the willingness to pay towards sustainability of the ecotourism resources at KKGP. The results show the price of bid, income, age, strata, origin and education level are the most important and significant factors that influence and determine the amount of conservation fee charged at KKGP. In the questionnaire the respondents, who are visitors to KKGP, were asked about their attitudes, opinion and willingness to pay. The respondents answer the maximum amount they were willing to pay for the non-market goods available at KKGP based on the circumstances, and their current income and expenses. The results of the survey indicate that visitors are willing to pay RM17.27 per visit towards sustainability. Besides that, the WTP between foreign and local visitors differs. The WTP of foreign visitors (RM 23.20) is much higher than the WTP of locals (RM13.96). Based on the number of visitors to KKGP in 2008 (167 152) the expected revenue that can be collected by the management is estimated at approximately RM 2 886 542.34 a year. Findings of this study may guide and assist policy makers in managing and developing recreational sites in Malaysia.